14. UPREGULATED PLK1 EXPRESSION CONFERS RADIATION RESISTANCE AND POOR PATIENT SURVIVAL OUTCOMES IN RECTAL CANCER. (February 2015) - Tut, Thein Ga; Lim, Stephanie; Dissanayake, Irani; Descallar, Joseph; Chua, Wei; Ng, Weng; De Souza, Paul; Bokey, Les; Shin, Joo-Shik; Lee, C. Soon
Abstract : Background and aim: Colorectal cancers (CRC) are common in Western countries. Death due to colorectal malignancy is the second commonest cause of cancer related death in Australia. Preoperative radiotherapy is commonly used to downstage rectal cancers in order to improve clinical outcome. However, the effectiveness of radiotherapy is highly variable between individual patients. Currently there are no reliable predictive biomarkers of radiation sensitivity. Hypothesis: PLK1 (polo-like kinase 1), the serine/threonine protein kinase, has crucial roles in cell cycle regulation, such as centrosome maturation, mitotic spindle formation and cytokinesis. PLK1 expression in colorectal cancer cell lines and in rectal tumour tissues may be related to radiation sensitivity of these tumours. PLK1 may be a possible biomarker that predicts the histological changes and clinical outcome in rectal cancer after radiotherapy. Methods: Archived rectal cancer tissue samples from a patient cohort (Sydney South West Pathology Service, n = 352) were constructed into tissue microarray (TMA) blocks. TMA slides were immunohistochemically stained with monoclonal anti-PLK1 anbtibodies. TMA immunohistochemistry (IHC) results of PLK1 expression were correlated with both histological tumour regression seen in the surgically resected bowel and with clinical survival times. Statistical analyses were performed with SPSS (IBM, version 21). Results: Rectal cancer patients with low PLK1 expression in their tumours have longer overall survival (univariate Kaplan–Meier analysis), and this trend remains significant in multivariate Cox regression analysis [hazard ratio of 0.474 (95% CI 0.265–0.849, p = 0.012)]. PLK1 expression correlated significantly with tumour regression grade (TRG) ( p = 0.039), with positive expression seen more commonly in poorly regressed tumours. Age and AJCC stage were other significant prognostic makers in our cohort. Conclusions: Current therapeutic management of rectal cancer can be improved with the availability of better predictive and efficient prognostic biomarkers. PLK1 expression appears to confer radiation resistance, with our results to date demonstrating a relationship between PLK1 immunostaining and treatment response in rectal cancers.